2020
DOI: 10.3389/fvets.2020.532763
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Epidemiology: Principles, Practice, Utility, and Lessons Learnt

Abstract: Participatory epidemiology (PE) evolved as a branch of veterinary epidemiology and has been largely employed for the control and early warning of infectious diseases within resource-limited settings. It was originally based on combining practitioner communication skills with participatory methods to facilitate the involvement of animal caretakers and owners (embracing their knowledge, experience, and motivations) in the identification and assessment of animal disease problems, including in the design, implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…The use of veterinary antimicrobials in Timor-Leste was even lower than countries such as New Zealand, Norway, and Iceland which are known to have some of the lowest use levels in the world [ 45 , 46 ]. The low level of use is likely due to the subsistence agriculture system in Timor-Leste [ 33 , 47 ] where there is poor access to veterinary services and medicines. The low level of use is also consistent with another study in Timor-Leste which showed that only 1% of backyard chicken farmers used commercial medicines in their animals [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of veterinary antimicrobials in Timor-Leste was even lower than countries such as New Zealand, Norway, and Iceland which are known to have some of the lowest use levels in the world [ 45 , 46 ]. The low level of use is likely due to the subsistence agriculture system in Timor-Leste [ 33 , 47 ] where there is poor access to veterinary services and medicines. The low level of use is also consistent with another study in Timor-Leste which showed that only 1% of backyard chicken farmers used commercial medicines in their animals [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participatory activities included community timelines, seasonal calendars, and collection of epidemiological information through proportional piling, ranking, tabulation and open discussion. Participatory epidemiological methods policies ( 17 , 18 ) are more sensitive than surveys for capturing local, contextual information and hold great utility for rapid assessments of disease impact in the field. To understand the vulnerability context of the community, seasonal calendars were developed to study disease and risk factors, population structures, disease features, biosecurity, disease timeline—historical data, disease impacts, strategies employed, plans for the future, indicative farm budget information, and responses to disease at community level.…”
Section: Methodsmentioning
confidence: 99%
“…It should also not be assumed, that disease is the most pressing problem and a more holistic, participatory and gender-sensitive approach to poultry production appears warranted. To appropriately tailor biosecurity and husbandry interventions to local conditions, it is essential that the various members (i.e., men, women and those of differing socio-economic and language groupings) of communities and households knowledgeable about poultry production be involved from the outset ( 26 ).…”
Section: Discussionmentioning
confidence: 99%